PERAN KELOMPOK TANI DALAM MENINGKATKAN PRODUKSI USAHATANI BAWANG MERAH - Berun, Sepriyandi Prayoga; Hendrik, Ernantje; Siubelan, Yacobus C.W. (Undana Press, 2023)
This research was conducted in Sumlili Village among two farmer groups, namely Kanaan and Berkat Usaha. The objectives of this research were to determine: 1) the characteristics of farmer groups in Sumlili Village, 2) the role of farmer groups in increasing shallot farming production in Sumlili Village, and 3) the factors associated with the role of farmer groups in increasing shallot farming production in Sumlili Village. The data used in this research consisted of primary and secondary data. The research method employed analytical tools such as Descriptive Analysis, Mean, Standard Deviation, and Spearman Rank. Microsoft Excel, SPSS, and a calculator were used as calculation software. The results of this research showed that: 1) Shallot farming in Sumlili Village was conducted on a total area of 3,400 ares (with an average area of 61.82 ares), resulting in a production of 49.24 tons and an average production of 0.014 tons per are or 1.4 tons per hectare. The production can be considered low compared to the national potential average of 15 tons per hectare for shallots. 2) The farmer groups played their roles based on three indicators, namely as a learning media (average score of 10.96), cooperation media (average score of 11.15), and production unit (average score of 10.44). All indicators showed that the farmer groups played a significant role with an average value of 10.82. 3) There was a significant relationship between the source of information factor and the role of farmer groups (0.038 < 0.05), and the facilities and production facilities factor also had a significant relationship with the role of farmer groups (0.049 < 0.05). However, factors such as farmers' age, land area, education level, farming experience, and the number of family dependents did not have a significant relationship with the role of farmer groups (p > 0.05)